Development of mobile application using QR code scanner to retrieve the validity of foundation status (QR-Foundation Status) / Norhisam Mistar - Mistar, Norhisam (2016)
This study presents the idea that the combination of Android Application and Quick Response codes scanner can contribute to the speed of getting information related to the status of a foundation. This combination make it easier for consumer to review information for at anywhere and anytime. The only Android Smartphone which stems from the need to download QR-Foundation Status at Android Play Store and continue to be used with ease. It helps the public to check apart should go to the official portal Bahagian Hal Ehwal Undang-Undang (BHEUU) to include the name for correcting it. This application can save time and users do not need to type anything for information. Mobile application system named QR-Foundation Status will be beneficial to the public to prevent fraud crimes such as using the foundation's name to apply for funding. The add-on that can be incorporated into the study later is integration between this mobile application with the system of Registrar of Society (ROS) and Jabatan Kebajikan Masyarakat (JKM). It reduces the establishment of foundation registration's fraud which often misused for the purpose of collecting donations by irresponsible person. This study also indirectly helps the authority agencies to handle fraud using children especially to raise funds illegally which gradually increased nowadays. It also determines new and effective solutions for receiving information more quickly and efficiently.